Astrocyte D-serine modulates the activation of neuronal NOS leading to the development of mechanical allodynia in peripheral neuropathy - Choi, Sheu-Ran; Roh, Dae-Hyun; Yoon, Seo-Yeon; Choi, Hoon-Seong; Kang, Suk-Yun; Han, Ho-Jae; Beitz, Alvin James; Lee, Jang-Hern (SAGE PUBLICATIONS INC, 2019)
Spinal D-serine plays an important role in nociception via an increase in phosphorylation of the N-Methyl-D-aspartate (NMDA) receptor GluN1 subunit (pGluN1). However, the cellular mechanisms underlying this process have not been elucidated. Here, we investigate the possible role of neuronal nitric oxide synthase (nNOS) in the D-serine-induced potentiation of NMDA receptor function and the induction of neuropathic pain in a chronic constriction injury (CCI) model. Intrathecal administration of the serine racemase inhibitor, L-serine O-sulfate potassium salt (LSOS) or the D-serine degrading enzyme, D-amino acid oxidase (DAAO) on post-operative days 0-3 significantly reduced the CCI-induced increase in nitric oxide (NO) levels and nicotinamide adenine dinucleotide phosphate-diaphorase staining in lumbar dorsal horn neurons, as well as the CCI-induced decrease in phosphorylation (Ser847) of nNOS (pnNOS) on day 3 post-CCI surgery. LSOS or DAAO administration suppressed the CCI-induced development of mechanical allodynia and protein kinase C (PKC)-dependent (Ser896) phosphorylation of GluN1 on day 3 post-surgery, which were reversed by the co-administration of the NO donor, 3-morpholinosydnonimine hydrochloride (SIN-1). In naive mice, exogenous D-serine increased NO levels via decreases in pnNOS. D-serine-induced increases in mechanical hypersensitivity, NO levels, PKC-dependent pGluN1, and NMDA-induced spontaneous nociception were reduced by pretreatment with the nNOS inhibitor, 7-nitroindazole or with the NMDA receptor antagonists, 7-chlorokynurenic acid and MK-801. Collectively, we show that spinal D-serine modulates nNOS activity and concomitant NO production leading to increases in PKC-dependent pGluN1 and ultimately contributing to the induction of mechanical allodynia following peripheral nerve injury.
Keywords: NITRIC-OXIDE SYNTHASE; NMDA-RECEPTOR PHOSPHORYLATION; PAIN SENSATION LIKE; PROTEIN-KINASE-C; INTRATHECAL INJECTION; THERMAL HYPERALGESIA; ACID RECEPTOR; NERVE INJURY; DORSAL-HORN; MOUSE MODEL